Modernizing Multilateralism and Markets - Zoellick, Robert B. (Washington, DC: World Bank, 2019)
Robert B. Zoellick, President the World Bank Group, delivered remarks on the following six strategic themes: a new multilateralism; priorities on a new steering group; international finance and development; the World Trade Organization (WTO) and the global trading system; energy and climate change; and fragile states and securing development.